OPTIMALISASI PLATFORM E-COMMERCE GLOBAL UNTUK MENINGKATKAN DAYA SAING UMKM PENGRAJIN ANYAMAN BAMBU DI DESA WATUONDO KAB. KONAWE KEPULAUAN - Muh. Ridwan; Handris Handris; Inten Suhartien; Muhamad Farih; Lucia Evianti Patulak; Wa Ode Dien Indalestari (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
Bamboo weaving SMEs have significant economic and cultural potential but face challenges in expanding access to global markets due to limited digital literacy and technology utilization. This study aims to examine the development of an e-commerce-based digitalization model to enhance SME competitiveness effectively and sustainably. Using a mixed methods approach, this research combines quantitative data from surveys of SME actors and qualitative data from interviews and direct observations. The findings indicate that digital literacy, training support, and infrastructure readiness are key determinants in driving e-commerce adoption. Meanwhile, major challenges include limited access to technology, language barriers, and lack of post-adoption assistance. These findings highlight the importance of a contextual, inclusive, and community-based digitalization approach. This study contributes to the formulation of adaptive digitalization strategies that support the sustainability and growth of SMEs in the global market.